Precise mode control of mid-infrared high-power laser diodes using on-chip advanced sawtooth waveguide designs - Shi, Jianmei; Yang, Chengao; Chen, Yihang; Wang, Tianfang; Yu, Hongguang; Cao, Juntian; Geng, Zhengqi; Wang, Zhiyuan; Wen, Haoran; Tan, Hao; Zhang, Yu; Jiang, Dongwei; et al. (High power laser science and engineering, 2024)
Power scaling in conventional broad-area (BA) lasers often leads to the operation of higher-order lateral modes, resulting in a multiple-lobe far-field profile with large divergence. Here, we report an advanced sawtooth waveguide (ASW) structure integrated onto a wide ridge waveguide. It strategically enhances the loss difference between higher-order modes and the fundamental mode, thereby facilitating high-power narrow-beam emission. Both optical simulations and experimental results illustrate the significant increase in additional scattering loss of the higher-order modes. The optimized ASW lasers achieve an impressive output power of 1.1 W at 4.6 A at room temperature, accompanied by a minimal full width at half maximum lateral divergence angle of 4.91°. Notably, the far-field divergence is reduced from 19.61° to 11.39° at the saturation current, showcasing a remarkable 42% improvement compared to conventional BA lasers. Moreover, the current dependence of divergence has been effectively improved by 38%, further confirming the consistent and effective lateral mode control capability offered by our design.